Feedlot performance of Nellore bulls fed high-concentrate diets containing the association of tannins and saponins with sodium monensin - Ferracini, Jéssica Geralda; Lelis, Ana Laura Januário [UNESP]; Polli, Daniel [UNESP]; Gasparim, Mariana Bassanezi; Feba, Luanda Torquato; do Prado, Ivanor Nunes; Millen, Danilo Domingues [UNESP] (Revista Brasileira de Zootecnia, 2024)
The objective of this study was to evaluate the performance of Nellore bulls finished in the feedlot and fed high-energy diets containing sodium monensin associated or not with tannins and saponins. Ninety-six Nellore bulls were used with an average initial body weight of 350.6±17.9 kg. The bulls were weight-blocked and randomly allocated to 12 pens, which were considered the experimental units. The treatments were assigned to the pens according to the blocks, as follows: sodium monensin (25 ppm; SM) and sodium monensin (25 ppm) plus tannins (350 ppm) and saponins (3.92 ppm, SM+TS). The bulls received an adaptation diet for the first 19 days, a growing diet from day 20 to day 59, and a finishing diet from day 60 to 98 of the experimental period. The animals were slaughtered after 98 days of study. The addition of tannins and saponins to the diets of feedlot Nellore cattle did not change the dry matter intake, hot carcass weight, and dressing percentage; however, it increased body weight by 2.0% and average daily gain by 5.4% and improved feed conversion by 4.3%. The addition of tannins and saponins to high-concentrate diets containing sodium monensin improves the productive performance of Nellore cattle finished in a feedlot for 98 days.
Keywords: additives; cattle; efficiency; intake